A smarter way to combat hunger - Sánchez, P.A. (2009)
This commentary argues that priorities to combat the number of undernourished people in the world should shift from prioritizing food aid to supplying impoverished farmers with training, access to markets, and farm equipment such as fertilizer and improved seed. The solution will be more effective and cheaper. The solution is posited due to estimates from the Food and Agriculture Organization of the United Nations suggesting that 963 million people in poor countries are hungry.